Exploring the Role of Artificial Intelligence (AI) Support in Assisting Students’ English-Speaking Skills - Pujo Pangestu, Hurip; Suwartono, Tono (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
This research explores the role of Artificial Intelligence (AI) support in helping students' English-speaking skills. With the increasing importance of speaking skills in academic, professional and social contexts, this research aims to analyze the role of AI assistance in helping students' English-speaking skills. This research uses descriptive qualitative methods with 4 sixth semester student participants from a private university in Purwokerto who often use AI to help their English-speaking skills. Data was collected through semi- structured interviews and analyzed using data reduction techniques, data presentation, and drawing conclusions. The research results show that AI makes a significant contribution to English language learning through personalization of learning, automatic evaluation. However, there are challenges in using AI such as lack of human interaction, limited features and AI not being able to understand complex situations. This research provides insight into the benefits and challenges of using AI in language learning, as well as its implications for the development of students' English-speaking skills.